2020
DOI: 10.18203/2394-6040.ijcmph20201056
|View full text |Cite
|
Sign up to set email alerts
|

Self-medication among Alexandria University students and effect of an educational intervention on their self-medication knowledge, attitudes and practices

Abstract: Background: Self-medication (SM) among university students is a growing prevalent public health concern worldwide. It is highly prevalent in developing countries. SM leads to serious consequences such as drug misuse/abuse and adverse drug reactions. The study aims to determine the prevalence of SM among university students in Alexandria, Egypt and to assess the effect of an educational intervention on their SM knowledge, attitudes and self-reported practices (KAP).Methods: The study was conducted among 400 stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…The prevalence of SM was estimated to be 79.5% among students of Alexandria University, Egypt, and 62.9% in students from the University of Mansoura, Egypt. [ 3 14 23 ] A recently study conducted in a medical university of Islamabad Pakistan reported an SM prevalence of 77%. [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The prevalence of SM was estimated to be 79.5% among students of Alexandria University, Egypt, and 62.9% in students from the University of Mansoura, Egypt. [ 3 14 23 ] A recently study conducted in a medical university of Islamabad Pakistan reported an SM prevalence of 77%. [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 25 ] Nevertheless, long waiting time at physician's clinics was also one of the minor factors (3.7%) for practicing SM in this study as well as many others. [ 3 14 23 27 ] As opposed to this, 59% of students from one African university cited this as a reason for SM. [ 28 ] Surprisingly, only 4.8% ( n = 9) had taken multivitamins in their SM practices in spite of the fact that 1.6% had reported paleness, and 0.5% had experienced a loss of weight.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations